Circulating exosomal microRNAs as novel potential detection biomarkers in pancreatic cancer - Wu, Lun; Zhou, Wen‑Bo; Zhou, Jiao; Wei, Ying; Wang, Hong‑Mei; Liu, Xian‑De; Chen, Xiao‑Chun; Wang, Wei; Ye, Lin; Yao, Li; Chen, Qin‑Hua; Tang, Zhi‑Gang (Oncology letters, 2020)
Circulating exosomal microRNAs (ex-miRNAs) are reflective of the characteristics of the tumor and are valuable biomarkers in different types of tumor. In addition, miRNAs serve important roles in tumor progression and metastasis. The present study aimed to investigate the circulating ex-miRNA-21 and miRNA-210 as novel biomarkers for patients with pancreatic cancer (PC). For this purpose, serum ex-miRNAs were extracted from the serum of patients with PC (n=30) and chronic pancreatitis (CP) (n=10) using an RNA isolation kit. For exosome identification in serum, transmission electron micrographs were used to determine crystalline structure, western blotting was used to identify exosomal markers, and NanoSight was used for nanoparticle characterization. The relative expression levels of ex-miRNAs were quantified using quantitative PCR and compared between patients with PC and CP. The expression levels of both ex-miRNA-21 and miRNA-210 were significantly higher in patients with PC compared with patients with CP (both P<0.001). However, no significant difference in the relative serum levels of free miR-21 and miR-210 was observed between the 2 groups of patients (both P>0.05). ex-miRNA-21 and miRNA-210 were associated with tumor stage, as well as other factors. The diagnostic potential of ex-miRNA-21 and miRNA-210 levels was 83 and 85%, respectively. In addition, when ex-miRNA and serum carbohydrate antigen 19-9 expression levels were combined, the accuracy increased to 90%. The present study identified that serum ex-miRNAs, miRNA-21 and miRNA-210 may be of value as potential biomarkers and therapeutic targets for the diagnosis and treatment of PC.